Effect of Ramadan fasting in patients with type 2 diabetes mellitus treated with sodium–glucose cotransporter 2 inhibitors: A systematic review and meta‐analysis. Issue 5 (13th January 2022) - Gad, Hoda; Al‐Nassr, Noor; Mohammed, Ibrahim; Khan, Adnan; MacDonald, Ross; Mussleman, Paul; Malik, Rayaz A.
ABSTRACT: Aims/Introduction: Sodium–glucose cotransporter 2 inhibitors (SGLT‐2i) improve glycemic control and weight, but might be associated with dehydration, hypotension and ketoacidosis, especially in patients with type 2 diabetes mellitus who fast during Ramadan. This meta‐analysis evaluates the effects of Ramadan fasting on patients with type 2 diabetes mellitus treated with SGLT‐2i. Materials and Methods: A literature search was carried out in PubMed, Embase and the Cochrane Library. Quality assessment was carried out using the ROBINS‐I and Cochrane tools for risk of bias, and analyses were carried out using RevMan version 5.3. Results: A total of five studies were included in this meta‐analysis. During Ramadan, there was a significant reduction in glycated hemoglobin ( P  < 0.00001) and diastolic blood pressure ( P  = 0.006), with a non‐significant trend for a reduction in weight ( P  = 0.44) and systolic blood pressure ( P  = 0.67). The number and severity of hypoglycemic episodes was lower in patients with type 2 diabetes mellitus treated with SGLT‐2i compared with sulfonylureas. There was no significant change in estimated glomerular filtration rate, β‐hydroxybutyrate, bicarbonate or anion gap. However, we identified considerable heterogeneity among studies, and a lack of head‐to‐head studies with structured outcome reporting on the risks and benefits of SGLT‐2i during Ramadan. Conclusions: This systematic review and meta‐analysis shows that patients with type 2 diabetes treated with SGLT2i's during Ramadan have an improvement in HbA1c, less hypoglycemia and no major adverse effects. Abstract : This meta‐analysis identifies an improvement in glycated hemoglobin, weight and diastolic blood pressure in patients treated with sodium–glucose cotransporter 2 inhibitors who fast during Ramadan.